A new class of symmetric bisbenzimidazole-based DNA minor groove-binding agents showing antitumor activity - Mann, J; Baron, A; Opoku-Boahen, Y; Johansson, E; Parkinson, G; Kelland, LR; Neidle, S (Journal of medicinal chemistry, 2001)
The synthesis and evaluation of the novel head-to-head bisbenzimidazole compound 2,2-bis[4'-(3 " -dimethylamino- 1 " -propyloxy)phenyl]-5,5-bi-1H-benzimidazole is described. An X-ray crystallographic study of a complex with the DNA dodecanucleotide sequence d(CGCGAATTCGCG) shows the compound bound in the A/T minor groove region of a B-DNA duplex and that the head-to-head bisbenzimidazole motif hydrogen-bonds to the edges of all four consecutive A:T base pairs. The compound showed potent growth inhibition with a mean IC50 across an ovarian carcinoma cell line panel of 0.31 muM, with no significant cross-resistance in two acquired cisplatin-resistant cell lines and a low level of cross-resistance in the P-glycoprotein overexpressing acquired doxorubicin-resistant cell line. Studies with the hollow fiber assay and in vivo tumor xenografts showed some evidence of antitumor activity.